LISA Pathfinder test-mass charging during galactic cosmic-ray flux short-term variations. (5th January 2015) - Grimani, C; Fabi, M; Lobo, A; Mateos, I; Telloni, D
Abstract: Metal free-floating test masses aboard the future interferometers devoted to gravitational wave detection in space are charged by galactic and solar cosmic rays with energies 100 MeV/n. This process represents one of the main sources of noise in the lowest frequency band ( 10 −3 Hz) of these experiments. We study here the charging of the LISA Pathfinder (LISA-PF) gold-platinum test masses due to galactic cosmic-ray (GCR) protons and helium nuclei with the Fluka Monte Carlo toolkit. Projections of the energy spectra of GCRs during the LISA-PF operations in 2015 are considered. This work was carried out on the basis of the solar activity level and solar polarity epoch expected for LISA-PF. The effects of GCR short-term variations are evaluated here for the first time. Classical Forbush decreases, GCR variations induced by the Sun rotation, and fluctuations in the LISA-PF frequency bandwidth are discussed.